Failure Analysis of Brake Panel on Automotive Braking System - Yoyok Winardi; Munaji Munaji (University of Muhammadiyah Malang, 2019)
This paper presents the results of a failure analysis investigation conducted in the braking componentof motorcycle. One of the components is the brake panel. This component has been replaced in the non-authorized dealer. After used within 3 months, the brake panels broken during the braking process. The investigation involves several procedures and testing techniques, including: visual observation, chemical composition testing, fractography and hardness testing. Based on the results of the chemical composition testing, the brake panels are made of aluminum alloy (Al-Si) series 4xxx. Fractography was performed in scanning electron microscopy (SEM) and optical microscopy (OM). Vickers hardness machine is used to test the hardness. The result of the observations indicate porosity along the fracture area. The result of the hardness testing shows that the distribution of hardness in different zones is very uniform. Based on the overall analysis, the failure of the brake panel caused by stress concentration. Porosity in the solid solutions of brake panel is the cause. The emergence of porosity was suspected an error during the casting process.